2021
DOI: 10.3390/cells11010110
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction as a Hallmark of Environmental Injury

Abstract: Environmental factors including diet, sedentary lifestyle and exposure to pollutants largely influence human health throughout life. Cellular and molecular events triggered by an exposure to environmental pollutants are extremely variable and depend on the age, the chronicity and the doses of exposure. Only a fraction of all relevant mechanisms involved in the onset and progression of pathologies in response to toxicants has probably been identified. Mitochondria are central hubs of metabolic and cell signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 90 publications
(103 reference statements)
0
19
0
Order By: Relevance
“…Exposure to external stimuli, such as multiple environmental contaminants, affects the normal structure and function of the mitochondria, leading to metabolic and functional diseases [ 21 , 22 ]. Recent studies have provided insights into the involvement of mitochondrial function defects that are induced by the toxicity of environmental contaminants [ 23 , 24 , 25 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to external stimuli, such as multiple environmental contaminants, affects the normal structure and function of the mitochondria, leading to metabolic and functional diseases [ 21 , 22 ]. Recent studies have provided insights into the involvement of mitochondrial function defects that are induced by the toxicity of environmental contaminants [ 23 , 24 , 25 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining the cellular mitochondrial health is mediated via different processes such as mitochondrial fission, fusion, biogenesis, and mitophagy [ 39 ]. Early studies have shown that an imbalance in the cellular energy demand due to environmental stress can alter the different mitochondrial processes and thus can adversely affect the overall mitochondrial quality [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has shown that AhR is involved in the regulation of cellular metabolism in many types of cells by acting as a TF to control the expression of metabolism-related genes, by interacting with intracellular signaling pathways related to metabolism, or by disturbing mitochondrial function 56, 57 . AhR is expressed by various immune cells, and its signaling exerts integrative effects on the cellular environment and metabolism of the immune responses 58 .…”
Section: Discussionmentioning
confidence: 99%